Heating, ventilation and air conditioning systems: Fault detection and isolation and safe parking. (4th January 2018) - Shahnazari, Hadi; Mhaskar, Prashant; House, John M; Salsbury, Timothy I.
Highlights: A FDI framework for sensor and actuator fault detection and isolation in VAV boxes of HVAC systems. Diagnosing multiple faults and faults that their effect gets masked by the controller. A safe parking strategy with energy saving capability for handling stuck dampers. Abstract: This work presents an integrated framework for fault detection and isolation (FDI) and fault tolerant control (FTC) of variable air volume (VAV) boxes, a common component of heating, ventilation and air conditioning (HVAC) systems. To this end, first a statistical model based FDI framework is designed using existing techniques such as principal component analysis (PCA) and joint angle analysis as a benchmark for comparison. Then a novel linear causal model based framework for FDI of multiple actuator and multiple sensor faults is designed and implemented and shown to possess superior FDI capabilities compared to the statistical model based framework. Finally, a safe parking strategy is designed and the ensuing energy savings for the case of stuck dampers demonstrated.